The Impact of Transformational Leadership and Work Environment on Performance Through Intrinsic Motivation as A Mediating Variable - Muhammad Teddy Gunawan; Slamet Ahmadi (Riviera Publishing, 2026)
This study aims to analyze the influence of transformational leadership and the work environment on employee performance, with intrinsic motivation as an intervening variable. The study was conducted on employees of the Regional Development Planning, Research, and Development Agency of Bogor Regency, with 62 respondents. The research approach used a quantitative method through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The sampling technique used was simple random sampling, with data collected through questionnaires. The results of the study indicate that transformational leadership influences performance, while the work environment does not. However, both factors influence intrinsic motivation. Furthermore, intrinsic motivation influences performance and mediates the relationship between transformational leadership and performance, as well as between the work environment and performance. Therefore, increasing intrinsic motivation can strengthen the influence of transformational leadership and the work environment on performance